MANAJEMEN HIPERTENSI GESTASIONAL: PENDEKATAN ASUHAN KEFARMASIAN - Sitta Hasanatin Sholihah (Yayasan Nusantara Hasana Berdikari, 2025)
Gestational hypertension is a condition characterized by an increase in blood pressure that occurs during pregnancy, usually after the 20th week. According to data from the World Health Organization (WHO), gestational hypertension affects approximately 6-8% of all pregnancies worldwide, making it one of the leading causes of maternal morbidity and mortality. This case study aims to analyze the therapeutic management of gestational hypertension in pregnant women according to the literature, following the principles of Evidence-Based Medicine (EBM). The presentation of this case study is expected to provide an approach to the management of gestational hypertension in pregnant women, in line with Pharmaceutical Care, to improve the quality of life for both mother and fetus. This research is a case report that uses a descriptive method by analyzing a patient's case. The analysis used to solve the problems in this patient's case uses the Subjective, Objective, Assessment, and Planning (SOAP) method. The subjective data analysis of the patient in this case includes a history of current illness, which is hypertension, a history of previous illness, which is hemorrhoids during the first childbirth, and a family history of illness, which is the patient's mother having a history of hypertension. The objective data obtained includes vital signs from March 7, 2018, which showed a blood pressure of 165/110 mmHg, body temperature of 36.8°C, pulse of 74 beats per minute, and respiratory rate of 22 breaths per minute. On March 8, 2018, the vital signs showed a blood pressure of 130/70 mmHg, body temperature of 36.8°C, pulse of 84 beats per minute, and respiratory rate of 22 breaths per minute. The laboratory examination results showed leukocytosis with a value of 13.4 Rb/MMK (normal value 4-11 Rb/MMK), elevated segmented neutrophils with a value of 76.3% (normal value 40-70%), and low blood sugar with a value of 65 (normal value 80-120). The assessment of the therapeutic dosage given to the patient, including Amoxicillin 500 mg 3 times a day to prevent infection, Nifedipine 10 mg 3 times a day to treat gestational hypertension, and Ultraproct N suppository 1 time a day to treat hemorrhoids, was found to be appropriate. The plan for the patient, Ny. E, includes continuing Nifedipine therapy until the target blood pressure is achieved (< 150/80-100 mmHg), dietary changes with a low-salt diet, and lifestyle modifications. In conclusion, the patient, Ny. E, experienced gestational hypertension with a blood pressure of 165/110 mmHg, which is classified as severe hypertension. The therapy given to the patient was found to be appropriate according to the guidelines.